The Application of Blockchain in Supply Chain Management ： Knowledge Mapping Analysis Based on Citespace - Zhang, Peng; T., Ramayah; Lo, May Chiun (ASIAN SCHOLARS NETWORK, 2023)
This study examines the present scholarly research on blockchain technology in supply chain management. The primary purpose of this working paper is to visualize and perform a scientometric review of 468 publications and research published between 2007 and 2021 from the Web of Science database. Co-author analysis, co-word analysis, and cocitation analysis highlight main concepts and research hotspots and provide light on important specializations and developing trends. This study primarily uses Citespace5.8. R1 to conduct a systematic analysis of author collaboration networks, keyword co-occurrence networks, keyword clustering, keyword burstiness, and literature co-citation graph spectrum networks in the domain of blockchain in supply chain management to identify the research state, development trend, hotspots, and frontiers. Research shows that :(1) since 2017, the literature on the application of blockchain in supply chain management has expanded rapidly. China and the United States are particularly advanced in this area compared to other nations. (2) The "blockchain in supply chain management" research mainly focuses on technical framework theory, which uses distributed ledger technology and smart contracts to control supply chain operations. Simultaneously, technical innovation should be combined with artificial intelligence, the Internet of Things, and other technologies to enhance the trust, transparency, traceability, performance index, and security of the supply chain. (3) The horizon of study in this area is the integration of RFID and blockchain technology for technical innovation in Industry 4.0, intending to improve and optimize each supply chain node.